1989
DOI: 10.1002/dc.2840050304
|View full text |Cite
|
Sign up to set email alerts
|

The significance of atypical apocrine cells in fine‐needle aspirates of the breast

Abstract: Apocrine metaplastic cells are frequently present in fine-needle aspirates (FNAs) of breast lesions, especially fibrocystic disease. Occasionally, apocrine cells may be atypical and present diagnostic difficulties. The morphologic features of six breast FNAs that contained atypical apocrine cells in breast aspirates. In the six abnormal cases, the large, pleomorphic, atypical apocrine cells were the predominant cell type and occurred singly and in syncytial tissue fragments. The cells had large, eccentric, ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
0
14
1
Order By: Relevance
“…This is reflected in the few false positive cases in the literature, which include apocrine adenosis involving two radial scars, 2,6 apocrine cells in a degenerated cyst 8 and two cases of atypical apocrine metaplasia. 5,10 The histopathologic findings in one cytologic case of "atypical apocrine metaplasia" was a "cyst lined with apocrine cells with papillary tufting and focal cribriform arrangement." The cells were described as being "focally crowded and the nuclei were enlarged."…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is reflected in the few false positive cases in the literature, which include apocrine adenosis involving two radial scars, 2,6 apocrine cells in a degenerated cyst 8 and two cases of atypical apocrine metaplasia. 5,10 The histopathologic findings in one cytologic case of "atypical apocrine metaplasia" was a "cyst lined with apocrine cells with papillary tufting and focal cribriform arrangement." The cells were described as being "focally crowded and the nuclei were enlarged."…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to benign apocrine cells, apocrine carcinoma is characterized by higher cellularity, increased number of single cells, syncytial tissue aggregates, higher nuclear/cytoplasmic ratio, larger nuclei, marked atypia, abnormal chromatin, multiple and pleomorphic macronucleoli, necrosis, absence of naked, bipolar nuclei and absence of other benign cellular elements. 5 Clinically, apocrine carcinomas tend to be > 2.0 cm in diameter. 10 Furthermore, women with apocrine carcinoma tend to be older by at least 20 years 10 than those who present with atypical apocrine adenosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Johnson et al reported that apocrine metaplastic cells were very often seen in FNAC of breast lesions, mainly in fibrocystic disease and those apocrine cells could be atypical and lead to difficulties in the diagnosis. 11 They also reported that in contrast to sparse distribution, huge and atypical nuclear status of apocrine carcinoma, apocrine cells in benign lesions such as atypical apocrine adenosis, apocrine adenoma, granular apocrine metaplasia, and degenerative cyst were round and uniform and formed more regular layers. 11 Apocrine cancers, as also seen in our case, are positive for GCDFP-15 with a high ratio.…”
Section: Medical Pathologymentioning
confidence: 99%
“…11 They also reported that in contrast to sparse distribution, huge and atypical nuclear status of apocrine carcinoma, apocrine cells in benign lesions such as atypical apocrine adenosis, apocrine adenoma, granular apocrine metaplasia, and degenerative cyst were round and uniform and formed more regular layers. 11 Apocrine cancers, as also seen in our case, are positive for GCDFP-15 with a high ratio. Honma et al showed that the tumor was stained well (75%) with GCDFP-15, while ER, PR, and Bcl-2 expressions were very low (3.8, 5.8, and 1.9%, respectively).…”
Section: Medical Pathologymentioning
confidence: 99%